Comparison of two warming methods in preventing perioperative hypothermia in children: forced air versus warmer - Sinafar, Sima; Maleki, Anahid; Ebrahimsoltani, Alireza; Khosravi, Rahman; Sadeghi, Maneli (Iranian Journal of Pediatric Surgery, 2018)
Introduction: Perioperative hypothermia is common during anesthesia and surgery and is accompanied by several complications. Compared to adults, children are at a greater risk of hypothermia and its complications. The aim of this study was to compare forced air and warmer in maintaining normothermia during pediatric surgery. Materials and Methods: This randomized controlled trial was performed on 90 children undergoing elective hernia repair equally distributed in three groups of warmer, forced air and control. Patients’ body temperature was recorded preoperatively, intraoperatively, at the end of surgery and at the end of the postoperative care unit (PACU) stay. Time between anesthetic discontinuation and tracheal extubation and duration of PACU stay were also noted. Results: Intraoperative and postoperative body temperature and body temperature on exit from PACU were significantly higher in forced air group in comparison to warmer and control groups and in warmer group in comparison to control group (P<0.05). Time between anesthetic discontinuation and tracheal extubation and duration of PACU stay were significantly shorter in forced air group compared to warmer and control groups and in warmer group compared to control group(P<0.05). Conclusion: In comparison between the two methods (Warmer vs. Forced air), we found that forced air was significantly more effective in maintaining normothermia during pediatric hernia repair.